Emerging role of stereotactic body radiotherapy in the treatment of pancreatic cancer. Issue 4 (April 2013) - Berber, Betul; Sanabria, Juan R; Braun, Kelly; Yao, Min; Ellis, Rodney J; Kunos, Charles A; Sohn, Jason; Machtay, Mitchell; Teh, Bin S; Huang, Zhibin; Mayr, Nina A; Lo, Simon S
The management of pancreatic cancer continues to be challenging. Despite surgical, genetic and molecular advances, its overall prognosis remains poor. Surgical resection is the only modality that offers a chance for a cure, with an overall survival rate of 10–20% at 5 years. However, only 20% of the patients are surgical candidates because of locally advanced disease or systemic stage at presentation. Conventional radiotherapy, with or without chemotherapy, has been used to treat patients with advanced-stage pancreatic cancer, an approach with high rates of local recurrence. Stereotactic body radiation therapy, also known as stereotactic ablative radiotherapy has emerged as a treatment modality that allows the precise delivery of a large ablative radiation dose to a tumor volume while sparing surrounding organs and tissues. Phase I and II studies have shown good rates of local control of the disease but rates of distant metastasis remain significant. Strategies to combine novel systemic therapy and stereotactic body radiation therapy are to be explored.